Association of serum beta-hCG and urine albumin-creatinine ratio with hypertensive disorders during pregnancy - Yadav, Kanishka; Tyagi, Mamta; Gupta, Smriti; Verma, Yamini; Kumar, Sandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preeclampsia with or without severe symptoms, chronic hypertension with or without superimposed pre-eclampsia/eclampsia, gestational hypertension, HELLP syndrome, or eclampsia all pose a significant risk of morbidity for both the mother and the unborn child. The aim of this study was to investigate if the albumin-to-creatinine ratio in urine spots and the serum beta-hCG level correlate with the hypertensive illness of pregnancy.” Method: “The current inquiry was conducted during the months of October 2020 and August 2022 at the obstetrics and gynaecology department of Subharti medical college in Meerut, Uttar Pradesh. The study was not open to women who were more than 20 weeks pregnant, had gestational diabetes mellitus, had more than one pregnancy, had chronic hypertension, chronic renal disease, chronic liver disease, cardiac disease, systemic lupus erythematosus, or haematological illnesses. We measured the levels of serum beta hCG and the urine albumin-creatinine ratio, and we compared them between the groups.” Results: After ensuring that each participant had given their informed permission, the trial comprised a total of 200 patients. In the hypertensive group of the participants in the study, 31% were between the ages of 21 and 35, and 29% were less than 20 years old. With increased beta hCG and UACR, there was a higher incidence of hypertensive retinopathy, acute renal failure, DIC, and PPH among the patients, as well as the poorest fetal outcomes. (p<0.05) Conclusions: The presence of a substantial relationship between hypertensive diseases and raised levels of beta-hCG during pregnancy, as well as a greater ratio of urine albumin to creatinine. There is a considerable increase in the incidence of fetal growth retardation, preterm, and mortality occurring within the uterus among mothers who have higher levels of beta-hCG and urine ACR.